2001
DOI: 10.1093/ajcn/74.4.464
|View full text |Cite
|
Sign up to set email alerts
|

n−3 Fatty acids and cardiovascular disease risk factors among the Inuit of Nunavik

Abstract: Consumption of marine products, the main source of EPA and DHA, appears to beneficially affect some cardiovascular disease risk factors. The traditional Inuit diet, which is rich in n-3 fatty acids, is probably responsible for the low mortality rate from ischemic heart disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
162
6
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(189 citation statements)
references
References 69 publications
17
162
6
4
Order By: Relevance
“…49 It has been suggested that traditional diet rich in fish and marine mammals was associated with a favorable level of serum lipids among Aboriginal people. [50][51][52] A recently published study in Greenland Inuit 50 reported that serum lipids were significantly associated with the degree of westernization. HDL cholesterol decreased and triglyceride increased with westernization.…”
Section: Discussionmentioning
confidence: 99%
“…49 It has been suggested that traditional diet rich in fish and marine mammals was associated with a favorable level of serum lipids among Aboriginal people. [50][51][52] A recently published study in Greenland Inuit 50 reported that serum lipids were significantly associated with the degree of westernization. HDL cholesterol decreased and triglyceride increased with westernization.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary transition away from traditional foods, which are rich in various nutrients (5), is one critical factor linking the lifestyle changes with the shifting pattern in health and disease. In that regard, alterations in dietary fat intake are of interest given their importance in the development of chronic disease risk (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The protective effects of HUFA n-3 are attributed to their various physiological functions, including their maintenance of normal biomembrane structure (3) and function and precursors of eicosanoids (24); their key regu-HUFA n-3 status and Canadian Inuit lation of genes involved in lipid homeostasis (3); and their anti-arrhythmic action (5,6 HUFA n-3 status and Canadian Inuit…”
Section: Introductionmentioning
confidence: 99%
“…Consistency of epidemiological data for fish intake/omega-3 biomarkers and CHD risk ■ between populations -Yes [46][47][48][49] ■ within populations -Yes [33,50];…”
mentioning
confidence: 99%